STRATEGI BERSAING RUMAH MAKAN HENI PUTRI KAILI - WENGKAU, RAYMONDO (Fakultas Ekonomi Universitas Tadulako, 2015)
Heni Putri Kaili Restaurant is located at Kaombona Street/ Kampung Nelayan No. 09 Talise, East Palu Sub-district, Palu City. Heni Putri Kaili restaurant has been established since 6 years ago, precisely on February 20th 2010. The owner of the restaurant is Mrs. Haeni R. Kara , S.Pd. The research intends to find out the competitive level faced by Heni Putri Kaili Restaurant among the restaurant industries in Palu City and to comprehend the alternative strategy that can be used by Heni Putri Kaili Restaurant. Data analysis methods used are Porter?s Five Forces analysis and the SWOT (Strength, Weakness, Opportunities, Threats) analysis. Based on Porter?s Five Forces analysis, the study concludes that Heni Putri Kaili restaurant experiences a great rivalry among the restaurant industries in Palu City, which includes the rivalry beetween the competitors from the similiar industry, the suplier?s supplying capacity, and the threat of substitutes products. The result of SWOT metric diagram and IE table suggests that Heni Putri Kaili Restaurant should focus on the diversifications strategy while improving the service and the strategy to increase the promotion of the main product together with other products that are still unfamiliar by the consumers/markets.